Can Faith-BasedCorrectional Programs Work? An Outcome Evaluation of the InnerChange Freedom Initiative in Minnesota. (July 2013) - Duwe, Grant; King, Michelle
This study evaluated the effectiveness of the InnerChange Freedom Initiative (InnerChange), a faith-based prisoner reentry program, by examining recidivism outcomes among 732 offenders released from Minnesota prisons between 2003 and 2009. Results from the Cox regression analyses revealed that participating in InnerChange significantly reduced reoffending (rearrest, reconviction, and new offense reincarceration), although it did not have a significant impact on reincarceration for a technical violation revocation. The findings further suggest that the beneficial recidivism outcomes for InnerChange participants may have been due, in part, to the continuum of mentoring support some offenders received in the institution and the community. The results imply that faith-based correctional programs can reduce recidivism, but only if they apply evidence-based practices that focus on providing a behavioral intervention within a therapeutic community, addressing the criminogenic needs of participants and delivering a continuum of care from the institution to the community. Given that InnerChange relies heavily on volunteers and program costs are privately funded, the program exacts no additional costs to the State of Minnesota. Yet, because InnerChange lowers recidivism, which includes reduced reincarceration and victimization costs, the program may be especially advantageous from a cost-benefit perspective.